Biodiversity conservation gaps in the Brazilian protected areas - Oliveira, Ubirajara; Soares-Filho, Britaldo Silveira; Paglia, Adriano Pereira; Brescovit, Antonio D.; Carvalho, Claudio J. B. de; Silva, Dasniel Paiva; Rezende, Daniella T.; Leite, Felipe Sá Fortes; Batista, João Aguiar Nogueira; Barbosa, João Paulo Peixoto Pena; Stehmann, João Renato; Ascher, John S.; et al. (Scientific Reports, 2017)
Although Brazil is a megadiverse country and thus a conservation priority, no study has yet quantified conservation gaps in the Brazilian protected areas (PAs) using extensive empirical data. Here, we evaluate the degree of biodiversity protection and knowledge within all the Brazilian PAs through a gap analysis of vertebrate, arthropod and angiosperm occurrences and phylogenetic data. Our results show that the knowledge on biodiversity in most Brazilian PAs remain scant as 71% of PAs have less than 0.01 species records per km2. Almost 55% of Brazilian species and about 40% of evolutionary lineages are not found in PAs, while most species have less than 30% of their geographic distribution within PAs. Moreover, the current PA network fails to protect the majority of endemic species. Most importantly, these results are similar for all taxonomic groups analysed here. The methods and results of our countrywide assessment are suggested to help design further inventories in order to map and secure the key biodiversity of the Brazilian PAs. In addition, our study illustrates the most common biodiversity knowledge shortfalls in the tropics.
Keywords: Gaps; Protected areas